Project management - Maylor, Harvey (Harlow, England ; New York : Financial Times Prentice Hall, 2010)
The book provides a comprehensive and contemporary account of all that you need to know about the theory and practice of Project Management with highlights.
Includes bibliographical references and index
rua 08/05/13
Loans
Keywords: Project management; Project process